2021
DOI: 10.1007/s13346-021-01002-8
|View full text |Cite
|
Sign up to set email alerts
|

Testing of aerosolized ciprofloxacin nanocarriers on cystic fibrosis airway cells infected with P. aeruginosa biofilms

Abstract: The major pathogen found in the lungs of adult cystic fibrosis (CF) patients is Pseudomonas aeruginosa, which builds antibiotic-resistant biofilms. Pulmonary delivery of antibiotics by inhalation has already been proved advantageous in the clinic, but the development of novel anti-infective aerosol medicines is complex and could benefit from adequate in vitro test systems. This work describes the first in vitro model of human bronchial epithelial cells cultivated at the air–liquid interface (ALI) and infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…aeruginosa biofilm-infected cystic fibrosis patient, a protocol was established to address especially three underrepresented conditions in such models: (1) growing a bacterial biofilm on top of tight monolayers of human bronchial epithelial cells, (2) air–liquid interface conditions to enable repeated deposition of anti-infective drugs as aerosols, and (3) monitor both bacterial growth and killing, as well as host cell viability and epithelial barrier function under such treatment for several days. In contrast to the lung in vivo , where biofilms may take a long time to develop, , growing bacterial biofilms on cultured epithelial cells is not trivial, as the latter will typically die within hours due to rapid bacterial overgrowth. , To overcome this problem, biofilms were pre-grown separately for 72 h and then transferred to monolayers of CFBE41o- cells, which had also been grown separately for 7 days under ALI conditions (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…aeruginosa biofilm-infected cystic fibrosis patient, a protocol was established to address especially three underrepresented conditions in such models: (1) growing a bacterial biofilm on top of tight monolayers of human bronchial epithelial cells, (2) air–liquid interface conditions to enable repeated deposition of anti-infective drugs as aerosols, and (3) monitor both bacterial growth and killing, as well as host cell viability and epithelial barrier function under such treatment for several days. In contrast to the lung in vivo , where biofilms may take a long time to develop, , growing bacterial biofilms on cultured epithelial cells is not trivial, as the latter will typically die within hours due to rapid bacterial overgrowth. , To overcome this problem, biofilms were pre-grown separately for 72 h and then transferred to monolayers of CFBE41o- cells, which had also been grown separately for 7 days under ALI conditions (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The biofilm suspension is then incubated for 1 h on top of the cells to allow sedimentation. Experiments from a previous publication have shown that longer incubation times than 1 h lead to disruption of the barrier and premature subsequent cell death, pointing to the fact that keeping living bacteria and host cells in equilibrium for a long time is not trivial . After that, ALI conditions were restored by removing the remaining liquid from the apical compartment.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thiyagarajan et al enhance the pulmonary delivery potential of antimycobacterial nanopharmaceuticals by spray-drying the nanoparticles to form lactose-leucine microparticles with potentially more favorable aerodynamic properties [15]. Along the same delivery route, the challenge of delivering large antiinfectious biologics, antibodies, is presented by Mayor et al [16] while Juntke et al present a novel model of human bronchial epithelial cells cultivated at the air-liquid interface (ALI) and infected with a Pseudomonas aeruginosa biofilm that could have a large impact on the testing of such aerosolized anti-infective nanoparticle delivery systems [17]. The use of lipid delivery systems and their potential to ameliorate antimicrobial therapeutic effects are expounded in Clive Prestidge's "Nano-fats for bugs" review [18] and highlighted again by Ryan et al exploration of solid lipid nanoparticles for delivery of dual-acting antimicrobial peptides [19].…”
mentioning
confidence: 99%